ANALISIS PENDAPATAN ASLI DAERAH PROVINSI JAWA TENGAH PERIODE 2018-2022 - Yayang Bella; Tri Purwani; Ika Listyawati (Universitas Sains dan Teknologi Komputer, 2023)
Local Own Revenue is income earned by a region that is collected based on regional regulations in accordance with statutory regulations. the research data used is secondary data obtained from UPPD Kota Semarang II in 2018-2022. the study population is the taxpayer and retribution. The number of samples for 5 consecutive years, so that the total research data amounted to 240 data selected using the saturation sampling method. This study used multiple regression analysis and SPSS. the result obtained is that motor vehicle tax revenue has a positive effect. Surface water tax revenues have a significant negative effect, and regional wealth usage retribution receipts have no effect on regional own-source revenues in Central Java province.